Penegakan Hukum Syaria’h Melalui Peraturan Daerah (Studi Kajian Perda Kabupubaten Bintan Nomor 6 Tahun 2011 Tentang Pengawasan dan Pengendalian Minuman Beralkohol) - Okparizan Okparizan (Jurnal Selat, 2013)
In order to against the activities of alcoholic beverages in Bintan Regency, Regional Government of Bintan launched Regional Regulation No. 6 of 2011 concerning supervision and control of alcoholic beverages. This research is descriptive and kualitatif methods is used as research methods. Research data sources is a primary and secondary data. The informations is gathering from a number of books and through direct interviews with respondents in Bintan Regency Area. As the result, this Regional Regulation still need a few correction. This regulation is considered weak because it has not touch the distributors of alcoholic beverages but only the merchants. If this going so, the activities of alcoholic beverages in Bintan Regency will remain. The punishment of Regional Regulation breakers is still not strong enough and there is no real action for drinkers. As for islamics perspective, this regulation is not worked. Because in Islam alcohol is definitely forbidden. For moslems specially, this alcoholic beverages activities still be a nuisance.However, so far this Regional Regulation is giving a positive effects for alcoholic activities in Bintan Regency. It can be seen with the activities pre and post publication of the regulation. At the end of writing this research, Author have a suggestions that might be could give a contributes. Bintan Regency Government and Law Enforcement of Bintan could increase the effort to reducing alcoholic beverages activities by establishing a special agency against alcoholism. And hopefully could makes Bintan Regency is a “Alcohol Free Zone”.